Genetic Expression Screening of Arsenic Trioxide-Induced Cytotoxicity in KG-1a Cells Based on Bioinformatics Technology - Li, Yahui; Feng, Yingjie; Si, Xiaohui; Zhao, Chenjin; Wang, Fanping; Niu, Xinqing (Frontiers in Genetics, 2021)
Acute myeloid leukemia is one of the malignant tumors of the hematopoietic system, and leukemia stem cells are responsible for AML chemoresistance and relapse. KG-1a cell is considered a leukemia stem cells-enriched cell line, which resistant to chemotherapy. Arsenic Trioxide (ATO) is effective against acute promyelocytic leukemia as first-line treatment, even as remission induction of relapsed cases. ATO has cytotoxic effect on KG-1a, but the mechanism remains unclear. Our results demonstrated that ATO inhibits cell proliferation, induces apoptosis, and arrests KG-1a cells in the G2/M phase. Using transcriptome analysis, we investigated the candidate target genes regulated by arsenic trioxide's role in KG-1a cell. The expression profile analysis showed that the ATO had significantly changed gene expression related to proliferation, apoptosis and cell cycle. Moreover, MYC, PCNA and MCM7 were identified as crucial nodes through protein-protein interaction (PPI) network analysis; meanwhile the expressions of them in both RNA and protein levels are down-regulated confirmed by qPCR and western blot. Thus, our study suggested that ATO inhibits the expression of MYC, PCNA, and MCM7 and leads to cell cycle arrest and apoptosis in KG-1a cells. Overall, this study provided reliable clues for improving the arsenic trioxide efficacy in AML.